Integrative taxonomy, larval biology and functional morphology of the little known gall-forming coral endoparasite Petrarca (Thecostraca: Ascothoracida) - Gregory A. Kolbasov; Alexandra S. Savchenko; Meng-Chen Yu; Yao-Feng Tsao; Monthon Ganmanee; Benny K. K. Chan (Zoological Journal of the Linnean Society, 2023)
Abstract Petrarca is an ascothoracidan endoparasite in scleratinian dendrophyllid corals. Petrarca can stimulate coral growth, forming a gall chamber to house itself inside the coral skeleton. The diversity, molecular phylogeny and feeding ecology of Petrarca are understudied. This is the first study of Petrarca to be based on light and scanning electron microscopy to document the fine-scale external and functional morphology of its trophi and other structures. A combined molecular and morphological approach revealed at least four closely related species of Petrarca, P. goanna, P. morula, Petrarca nozawai sp. nov. and Petrarca rubus sp. nov. in Turbinaria and Astreopora corals in Asia. Carapace shape and fine morphology, ultrastructure of the antennular aesthetasc, morphological characteristics of the trophi and the shape and size of the penis rami are diagnostic characters. Several morphological characters, which are all probably synapomorphies, have been proposed to distinguish the genus Petrarca from other Ascothoracida. Mouthparts morphology of Petrarca are developed for cutting and chewing, rather than for piercing and sucking as in many other Ascothoracida. The external surface of the carapace of Petrarca is ornamented with densely packed secretory papillae used putatively for the chemical dissolution of the substrate necessary for the formation of the gall chamber.
Keywords: Coral and Marine Ecosystems Studies; Crustacean biology and ecology; Marine Biology and Ecology Research